Influence of recovery manipulation after hyperlactemia induction on the lactate minimum intensity - Paulino Ribeiro, Luiz Fernando; Santana Goncalves, Cassio Gustavo; Kater, Daniele Preto; Spiguel Lima, Manoel Carlos; Gobatto, Claudio Alexandre [UNESP] (Springer, 2009)
This study analyzed the influence of recovery phase manipulation after hyperlactemia induction on the lactate minimum intensity during treadmill running. Twelve male runners (24.6 +/- A 6.3 years; 172 +/- A 8.0 cm and 62.6 +/- A 6.1 kg) performed three lactate minimum tests involving passive (LMT(P)) and active recoveries at 30%vVO(2max) (LMT(A30)) and 50%vVO(2max) (LMT(A50)) in the 8-min period following initial sprints. During subsequent graded exercise, lactate minimum speed and VO(2) in LMT(A50) (12.8 +/- A 1.5 km h(-1) and 40.3 +/- A 5.1 ml kg(-1) min(-1)) were significantly lower (P < 0.05) than those in LMT(A30) (13.3 +/- A 1.6 km h(-1) and 42.9 +/- A 5.3 ml kg(-1) min(-1)) and LMT(P) (13.8 +/- A 1.6 km h(-1) and 43.6 +/- A 6.1 ml kg(-1) min(-1)). In addition, lactate minimum speed in LMT(A30) was significantly lower (P < 0.05) than that in LMT(P). These results suggest that lactate minimum intensity is lowered by active recovery after hyperlactemia induction in an intensity-dependent manner compared to passive recovery.
Keywords: Lactate minimum; Anaerobic threshold; Recovery; Running; Treadmill